Peripheral Blood Circular RNAs as a Biomarker for Major Depressive Disorder and Prediction of Possible Pathways - Zhang, Dandan; Ji, Yao; Chen, Xiongjin; Chen, RunSen; Wei, Yaxue; Peng, Qian; Lin, Juda; Yin, Jingwen; Li, Hezhan; Cui, Lili; Lin, Zhixiong; Cai, Yujie (Frontiers in Neuroscience, 2022)
Circular RNAs (circRNAs) are highly expressed in the central nervous system and have been reported to be associated with neuropsychiatric diseases, but their potential role in major depressive disorder (MDD) is still unknown. Here, we demonstrated that there was a disorder of circRNAs in the blood of MDD patients. It has been preliminarily proved that hsa_circ_0002473, hsa_circ_0079651, hsa_circ_0137187, hsa_circ_0006010, and hsa_circ_0113010 were highly expressed in MDD patients and can be used as diagnostic markers for MDD. Bioinformatics analysis revealed that hsa_circ_0079651, hsa_circ_0137187, hsa_circ_0006010, and hsa_circ_0113010 may affect the neuroplasticity of MDD through the ceRNA mechanism.